Realizing Green Economy: Synergies Between Waste Management and Economic Growth In The Oil And Gas Sector In Indonesia - Akbar, Muhammad Sandi; Adnan, Muhammad; Azra, Uliya (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
The implementation of a green economy is a key strategy in promoting sustainable development, especially in strategic sectors such as oil and gas in Indonesia. Green economy aims to improve human welfare in a sustainable manner by minimizing risks and pressures on the environment. This study aims to analyze the causality relationship between Gross Regional Domestic Product (GRDP), waste generation, population density, and energy use. The method used is panel data analysis with the Vector Error Correction Model (VECM) approach, which is able to identify long-term and short-term relationships between variables. The results show that there is a unidirectional causality relationship between waste generation and GRDP, as well as between population density and GRDP. In the long run, there is a significant relationship between population density and regional economic growth. Meanwhile, in the short term, there is a relationship between GRDP and population density. These findings emphasize the importance of waste management and population planning as an integral part of green economic development strategies in the oil and gas sector. This research contributes to the strengthening of environment-based policies that support the integration between economic development and ecosystem sustainability.